The Quran And Positive Law: A Philosophical Review In A Normative Legal Perspective - Adam Ibrahim, Faisol Mahmoud; Arifin, Moh Aziz (Universitas Islam kadiri, 2025)
This study aims to examine the relationship between the Qur'an as a source of Islamic law and positive Indonesian law from a philosophical perspective. Specifically, this study aims to understand the position of legal values ​​in the Qur'an towards the formation of positive law, as well as to examine the philosophical implications of the differences in the normative basis of the two. This title is important to study because in the practice of the national legal system, there is often a tug-of-war between legal values ​​derived from religion and the modern legal system rooted in the secular Western tradition. Given that Indonesia is a country with a Muslim majority population, the relevance of the Qur'an in the formation of law cannot be ignored, both in terms of legal ethics, justice values, and the formation of written legal norms. This study is formulated through two main questions: (1) What is the position of the Qur'an as a source of legal values ​​in the construction of positive law in Indonesia? and (2) What are the philosophical implications of the differences in the normative basis between the Qur'an and positive law towards the formation of legislation? To answer these questions, the method used is the normative legal research method with a legal philosophy approach and a legislative approach. The main data sources consist of primary legal materials in the form of laws and regulations and interpretations of legal verses in the Qur'an, as well as secondary legal materials such as Islamic legal literature and legal philosophy theories. The results of the study indicate that the Qur'an contains universal justice values ​​that are in line with the basic principles of positive law, such as justice, welfare, and legal certainty. Although there are differences in the form and structure of law, philosophically, both can complement each other within the framework of developing a just national law. This study recommends an integrative approach in formulating positive law that is not only based on legal-formal rationality, but also considers transcendental values ​​that originate from revelation.